At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Get quick and reliable solutions to your questions from a community of seasoned experts on our user-friendly platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
Certainly! Let's solve the equation step-by-step.
We are given the equation:
[tex]\[ w(w-2)(6w + 5) = 0 \][/tex]
To find the solutions, we need to determine the values of [tex]\( w \)[/tex] that make the equation equal to zero. This is a factored polynomial equation, and we can use the Zero Product Property, which states that if a product of factors is zero, then at least one of the factors must be zero.
Let's consider each factor individually:
1. First factor: [tex]\( w \)[/tex]
We set the first factor equal to zero:
[tex]\[ w = 0 \][/tex]
Therefore, one solution is:
[tex]\[ w = 0 \][/tex]
2. Second factor: [tex]\( w - 2 \)[/tex]
We set the second factor equal to zero:
[tex]\[ w - 2 = 0 \][/tex]
Solving for [tex]\( w \)[/tex], we get:
[tex]\[ w = 2 \][/tex]
Therefore, another solution is:
[tex]\[ w = 2 \][/tex]
3. Third factor: [tex]\( 6w + 5 \)[/tex]
We set the third factor equal to zero:
[tex]\[ 6w + 5 = 0 \][/tex]
Solving for [tex]\( w \)[/tex], we subtract 5 from both sides:
[tex]\[ 6w = -5 \][/tex]
Then, we divide both sides by 6:
[tex]\[ w = -\frac{5}{6} \][/tex]
Therefore, the third solution is:
[tex]\[ w = -\frac{5}{6} \][/tex]
Putting it all together, the solutions to the equation [tex]\( w(w-2)(6w+5) = 0 \)[/tex] are:
[tex]\[ w = 0, \quad w = 2, \quad \text{and} \quad w = -\frac{5}{6} \][/tex]
Hence, the complete set of solutions is:
[tex]\[ \boxed{[-\frac{5}{6}, 0, 2]} \][/tex]
We are given the equation:
[tex]\[ w(w-2)(6w + 5) = 0 \][/tex]
To find the solutions, we need to determine the values of [tex]\( w \)[/tex] that make the equation equal to zero. This is a factored polynomial equation, and we can use the Zero Product Property, which states that if a product of factors is zero, then at least one of the factors must be zero.
Let's consider each factor individually:
1. First factor: [tex]\( w \)[/tex]
We set the first factor equal to zero:
[tex]\[ w = 0 \][/tex]
Therefore, one solution is:
[tex]\[ w = 0 \][/tex]
2. Second factor: [tex]\( w - 2 \)[/tex]
We set the second factor equal to zero:
[tex]\[ w - 2 = 0 \][/tex]
Solving for [tex]\( w \)[/tex], we get:
[tex]\[ w = 2 \][/tex]
Therefore, another solution is:
[tex]\[ w = 2 \][/tex]
3. Third factor: [tex]\( 6w + 5 \)[/tex]
We set the third factor equal to zero:
[tex]\[ 6w + 5 = 0 \][/tex]
Solving for [tex]\( w \)[/tex], we subtract 5 from both sides:
[tex]\[ 6w = -5 \][/tex]
Then, we divide both sides by 6:
[tex]\[ w = -\frac{5}{6} \][/tex]
Therefore, the third solution is:
[tex]\[ w = -\frac{5}{6} \][/tex]
Putting it all together, the solutions to the equation [tex]\( w(w-2)(6w+5) = 0 \)[/tex] are:
[tex]\[ w = 0, \quad w = 2, \quad \text{and} \quad w = -\frac{5}{6} \][/tex]
Hence, the complete set of solutions is:
[tex]\[ \boxed{[-\frac{5}{6}, 0, 2]} \][/tex]
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.